Evaluation of SPADI and VAS in stroke patients with hemiplegic shoulder pain: A comparative study - Rawal, Hardik; Lohar, Deepak; Khan, Jafar; Warsi, Rahat Khan; Menria, Shubham; Balala, Deepika; Rai, Richa Hirendra; Pal, Renuka; Malvi, Ruchit; Jain, Rajshree (Journal of Neonatal Surgery, 2025)
Background: This study aims to evaluate the effectiveness of SPADI and VAS as measurement tools in assessing shoulder pain in stroke patients with hemiplegia. Given the impact of accurate pain assessment on rehabilitation outcomes, the study is designed to compare these tools to determine their reliability and usefulness in clinical settings for managing hemiplegic shoulder pain. Methodology & Results: This 12-month experimental study at Pacific Medical University enrolled 60 stroke patients (≥40 years) with hemiplegic shoulder pain and subluxation. Approved by the Institutional Ethics Committee, it utilized VAS and SPADI to assess pain and shoulder function. Exclusions included vulnerable diseases, tape allergy, and shoulder fractures. Informed consent was obtained, and patient confidentiality was ensured. The analysis revealed that SPADI effectively measured both pain and disability in stroke patients with hemiplegic shoulder pain (HSP), Comparative assessment showed consistent patterns between SPADI and VAS scores. Spearman’s correlation analysis demonstrated a significant positive correlation between SPADI and VAS scores Conclusion: SPADI assesses pain and disability; VAS measures pain intensity quickly. This indicating strong association in pain evaluation.